Intra-RNA cross-linking in Escherichia coli 30S ribosomal subunits: selective isolation of cross-linked products by hybridization to specific cDNA fragments. - Stiege, W (1988)
M13 clones were constructed with cDNA inserts corresponding to specific regions of E. coli ribosomal RNA. The DNA from the clones was immobilized by coupling to diazobenzyloxymethyl cellulose, and was used for the selective isolation by hybridization of cross-linked RNA complexes containing the complementary sequences. Immobilized DNA samples with inserts complementary to four different regions covering bases 735-1384 of the 16S RNA were hybridized with a mixture of 16S RNA fragments generated by partial digestion of 30S subunits that had been cross-linked by ultraviolet irradiation in vivo. After dehybridization, the individual RNA fragments and cross-linked complexes were separated by gel electrophoresis and analysed by our usual procedures. Nine cross-links are described; four of these are hitherto unobserved "secondary structural" cross-links, and one is a new "tertiary structural" cross-link between positions 243-247 and 891-894 of the 16S RNA.